Fuzzy Support System for Total Hip Arthroplasty Stem by Ultrasonic Intraoperative Measurement - Naomi Yagi; Yutaka Hata; Nao Shibanuma (Advances in Fuzzy Systems)
This paper describes a fuzzy system of stem implantation on total hip arthroplasty by an ultrasonic device. The system can perform automatic and accurate assessment in the surgery. In this system, we employ a single ultrasonic probe whose center frequency is 1,000 Hz. We detect the acoustic signals when knocking the inserted stem with a hammer. We then have a correlation between the degree of tightening and the attenuation time of acoustic signal. That is, the higher tightened degree implies shorter attenuation period. The support system selects the most suitable stem size by fuzzy inference with respect to the attenuation time and its difference time from correct stem to one larger size stem which dynamically adapts to each patient. As a result, we successfully determined the suitable stem in comparison to the results of the practical surgery.